(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In this article, the authors widely disclose various beliefs, rites, customs and traditions of the Kazakh people regarding the birth of a child. The purpose of this article is a comprehensive review of the meaning of prophetic dreams associated with the birth of a child, pilgrimage to holy places for receiving good signs, the ceremony of placing the baby in the cradle – a besik, cutting the ropes during the first steps of the child. Despite the fact that various scientific works were published on this topic, the authors first attempted to analyze this issue in close connection with folklore, with symbols and world background principles. The theme of the genesis of ancient beliefs, preserved in Kazakh myths and fairy tales, is separately touched upon. Also, the authors gave a systematic analysis of the data of the tradition on the basis of religious beliefs. Actuality of work consists in the systematic analysis of current known traditions and their reflection in oral literature. Another important feature of the article is a detailed analysis of Western scientific research on this topic. The main results of the research work can be used for further anthropological study of the issue under study. In conclusion, the authors give recommendations and suggestions for further research on this topic. Key words: Baby, celebration of a childbirth (literally: «shildehana»), cradle (literally: «Besik»), ritual, undershirts for a baby (literally «dog shirt»).